Deuterium MRS of early treatment‐induced changes in tumour lactate in vitro. (18th August 2021) - Tan, Josephine L.; Djayakarsana, Daniel; Wang, Hanzhi; Chan, Rachel W.; Bailey, Colleen; Lau, Angus Z.
Abstract : Elevated production of lactate is a key characteristic of aberrant tumour cell metabolism and can be non‐invasively measured as an early marker of tumour response using deuterium ( 2 H) MRS. Following treatment, changes in the 2 H‐labelled lactate signal could identify tumour cell death or impaired metabolic function, which precede morphological changes conventionally used to assess tumour response. In this work, the association between apoptotic cell death, extracellular lactate concentration, and early treatment‐induced changes in the 2 H‐labelled lactate signal was established in an in vitro tumour model. Experiments were conducted at 7 T on acute myeloid leukaemia (AML) cells, which had been treated with 10 μg/mL of the chemotherapeutic agent cisplatin. At 24 and 48 h after cisplatin treatment the cells were supplied with 20 mM of [6, 6′‐ 2 H2 ]glucose and scanned over 2 h using a two‐dimensional 2 H MR spectroscopic imaging sequence. The resulting signals from 2 H‐labelled glucose, lactate, and water were quantified using a spectral fitting algorithm implemented on the Oxford Spectroscopy Analysis MATLAB toolbox. After scanning, the cells were processed for histological stains (terminal deoxynucleotidyl transferase UTP nick end labelling and haematoxylin and eosin) to assess apoptotic area fraction and cell morphology respectively, while a colorimetric assay was used to measure extracellular lactate concentrations in the supernatant. Significantly lower levels of 2 H‐labelled lactate were observed in the 48 h treated cells compared with the untreated and 24 h treated cells, and these changes were significantly correlated with an increase in apoptotic fraction and a decrease in extracellular lactate. By establishing the biological processes associated with treatment‐induced changes in the 2 H‐labelled lactate signal, these findings suggest that 2 H MRS of lactate may be valuable in evaluating early tumour response. Abstract : Significant reductions in the deuterium ( 2 H)‐labelled lactate signal as early as 48 h after cisplatin treatment were measured using 2 H MRS at 7 T in an in vitro tumour model. These changes were significantly correlated with histologically confirmed apoptotic cell death and decreased extracellular lactate concentration.